Efeitos do ultrassom na preparação de emulsões do fluconazol usando líquidos iônicos N-alquil-N-metilimidazolíneos - Hennemann, Bruno Luís (2020)
Fluconazole is an active drug against a wide spectrum of species of fungi, this compound is used to treat superficial and systemic fungal infections. However, this medicine has dissolution problems, which causes limitations in the preparation and release of this drug. This limitation can be overcome by preparing emulsions. Ultrasound (US) is considered one of the most efficient and effective methods for preparing emulsions. Due to their amphiphilic characteristics, ionic liquids (ILs) based on imidazoline have potential application as a surfactant. Thus, combining US and LIs can be an alternative to prepare stable and simpler emulsions of fluconazole. Therefore, the objective of this work was to evaluate the influence of US on the properties of the fluconazole emulsion prepared using ILs derived from imidazole. Properties such as particle size, polydispersity index, morphology, encapsulation efficiency, viscosity, stability and release kinetics were evaluated. The preparation method (mechanical stirring - MS and US), the amplitude of the US (20% and 40%), size of the IL side chain (C12MIM[Br] or C16MIM[Br]) and IL concentration (1.5, 2.4 and 3.6 mM for C12MIM[Br] and 1.3, 2.06 and 3.1 mM for C16MIM[Br]) were evaluated. The results showed particle size and a lower polydispersity index for emulsions prepared in the US than in systems prepared by AM. This shows that the US was efficient in decreasing the particle size and polydispersity index of emulsions with ILs. TEM images proved that the particle morphology and the stability of the emulsions containing C16MIM[Br] are dependent on the preparation method and the concentration of IL. The emulsions prepared in the US showed spherical particles and an increase in stability compared to emulsions prepared by MS. The creaming and flocculation phenomena were less pronounced in systems with a higher concentration of IL. In all cases, the US with 40% amplitude increased the efficiency of the encapsulation. The use of US in the preparation of emulsions demonstrated a decrease in the viscosity of systems containing C12MIM[Br], although in general all emulsions had viscosity close to that of water and emulsions containing IL C16MIM[Br] had the lowest viscosities between the systems studied. In addition, all emulsions showed pseudo-plastic behavior. The drug release kinetics did not show any dependence on the preparation method, but on the type of IL - emulsions containing IL C16MIM[Br] showed a more controlled release and a lower total drug release than emulsions containing IL C12MIM[Br] in most cases. The DOSY experiments demonstrated that the addition of medium chain triglycerides (MCT) decreases the diffusion of ILs in the emulsion. In addition, the MCT titration experiments on the IL performed on the 1H NMR showed variation in the chemical displacement and multiplicity of the IL signals, which indicates interaction between the MCT and the IL. Finally, the emulsion stability results at 25 oC and 37 oC (body temperature) demonstrated that the use of US was one of the factors responsible for increasing the stability of the systems containing IL C16MIM[Br], since the instability index was lower for systems prepared by high energy. However, for emulsions containing C12MIM[Br], the instability index of emulsions prepared by US was higher than the index for emulsions prepared by MS, indicating that high energy causes destabilization of the emulsion. In summary, US was an effective method for preparing stable emulsions of fluconazole using C12MIM[Br] and C16MIM[Br] without additional surfactant. The concentration of ILs to prepare these emulsions was lower than the concentration of conventional surfactant, exhibiting the potential synergistic effects of ILs and US in the emulsion preparation of insoluble drugs.